Epidemiology, Causes and Prevention of Car Rollover Crashes with Ejection - El-Hennawy, HM (Medknow Publications & Media Pvt Ltd, 2014)
Rollover crashes (ROCs) are responsible for almost a third of all highway vehicle occupant fatalities. Although ROCs are common and serious mechanism of injury, ROCs are under-reported. To analyze the causes, mechanism, impact and prevention of ROCs, we reviewed the literature between 1984 and 2013. By utilizing the search engines PubMed, MEDLINE and EMBASE by using key words “ROCs” “Ejection” and “vehicle” the initial search yielded 241 abstracts, of which 58 articles were relevant. Most of the articles were either retrospective or experimental studies funded by automobile companies. All vehicles are susceptible to rollovers to certain extents. Despite continuing innovation in vehicles’ safety, human factor is pivotal in prevention of ROCs. Distracted driving, speeding and drinking escalate the chances of rollover crashes. Wearing a seatbelt greatly improves the chances of surviving a ROC.